PERANCANG PROGRAM KAMPANYE “BERSINAR” POLDA JATIM DENGAN TEKNIK SERIES CAMPAIGNDALAM UPAYA MEMBERANTAS NARKOBA - Apriannoor, Ilham; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
Now the government is intensively combating drugs , the government gave orders to every ministry / agency fight against drugs . Given the order , the police area of East Java ( East Java Police ) also participate in helping to combat drugs in the program